2015
DOI: 10.1002/joc.4420
|View full text |Cite
|
Sign up to set email alerts
|

Extreme seasonal droughts and floods in Amazonia: causes, trends and impacts

Abstract: This paper reviews recent progress in the study and understanding of extreme seasonal events in the Amazon region, focusing on drought and floods. The review includes a history of droughts and floods in the past, in the present and some discussions on future extremes in the context of climate change and its impacts on the Amazon region. Several extreme hydrological events, some of them characterized as 'once in a century', have been reported in the Amazon region during the last decade. While abundant rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
581
0
33

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(640 citation statements)
references
References 143 publications
(374 reference statements)
26
581
0
33
Order By: Relevance
“…Other studies on climate and hydrometeorological trends in the Amazon do not demonstrate unidirectional trends in large-scale precipitation or river flows (Marengo and Tomasella 2012;Marengo and Espinoza 2015). According to Dantas et al (2015) positive trends, but no statistical significance of meteorological variables are related to the absence of long-term data series.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies on climate and hydrometeorological trends in the Amazon do not demonstrate unidirectional trends in large-scale precipitation or river flows (Marengo and Tomasella 2012;Marengo and Espinoza 2015). According to Dantas et al (2015) positive trends, but no statistical significance of meteorological variables are related to the absence of long-term data series.…”
Section: Discussionmentioning
confidence: 94%
“…The years of lower rainfall also exhibited effects on the flow of Curuá-Una reservoir. In particular, 1998 was an extremely dry year for much of the Amazon basin, with serious consequences in the transport, health, agriculture and energy and water supply sectors Tomasella et al 2010;Marengo and Espinoza 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At national or continental scales, larger-scale drivers such as El Niño and La Niña events in the Pacific (e.g. Tomasella et al, 2011;Marengo and Espinoza, 2016), switches in Atlantic temperatures (Wilby, 2001;Folland et al, 2015), and tropical cyclones (e.g. Kam et al, 2013;Patterson et al, 2013) have been shown to be a factor in drought termination events.…”
Section: Droughtmentioning
confidence: 99%
“…All of these are important areas for research in modeling carbon release from soils (Lehmann and Kleber 2015). Climate change is expected to affect both temperature and humidity, with longer and more severe droughts together with higher temperatures in Amazonia, especially southern Amazonia (Fu et al 2013;Marengo and Espinoza 2016). Slow-turnover soil organic matter is more sensitive to release under warming than is fast turnover organic matter (Conant et al 2008;Craine et al 2010;Davidson and Janssens 2006).…”
Section: Soil Carbonmentioning
confidence: 99%